Green technology: synthesis of iron-modified biochar derived from pine cones to remove azithromycin and ciprofloxacin from water - Aziz, Sadia; Anbreen, Sundus; Iftikhar, Iqra; Fatima, Tabassum; Iftikhar, Aqsa; Ali, Liaqat (Frontiers in Environmental Science, 2024)
The rise of antibiotic pollutants in water threatens ecosystems and human health. Iron-modified biochar (BC) exhibits adsorption properties and offers a promising approach for effective environmental remediation. The current study explored the potential of iron-loaded biochar synthesized from pine cones for antibiotic removal from water. In this study, pine cones, a sustainable and renewable source, were used to produce iron-modified biochar and employed to remove azithromycin, ciprofloxacin, and their mixture from aqueous solutions. Biochar was synthesized through pyrolysis and modified by the addition of iron salts. The analysis of iron-modified biochar by Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and scanning electron microscopy (SEM) suggested a crystalline structure rich in minerals and functional groups (O–H, C=O, and C≡C) and loaded with iron, having plate-like roughness and distorted morphology along with sharp edges and corners. Antibiotic removal was evaluated by changing physical parameters, including biochar dose, pH, and temperature. The maximum removal percentages of azithromycin, ciprofloxacin, and their mixture were obtained as 87.8%, 91.3%, and 84%, respectively, at low pH, a low Fe-modified biochar dose, and higher temperature. Application of kinetic models suggested that the adsorption of antibiotics on iron-modified biochar is more inclined toward pseudo-second-order (R2 > 0.98) kinetics, indicating a chemisorption nature of the adsorption process. The findings highlight the potential of iron-modified biochar for removing antibiotics from aqueous solutions.